2013
DOI: 10.1017/s031716710001427x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Technique on Cushing Disease Outcome Using Strict Remission Criteria

Abstract: 334Cushing's Disease (CD) is the commonest cause of endogenous hypercortisolemia 1 and is associated with significant morbidity and mortality. [2][3][4] Transsphenoidal pituitary surgery remains the first line treatment for this condition with reported remission rates of 52% to 89%. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Many attempts have been made to identify factors that would predict sustained remission after surgical intervention. Suggested factors include smaller adenomas and the confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 45 publications
(65 reference statements)
2
31
0
Order By: Relevance
“…Many centers have replaced the transnasal route with an endoscopic endonasal approach (37), but both methods can be effective (38). Successful resection is most likely when performed by an experienced neurosurgeon who has a high volume of these cases.…”
Section: Evidencementioning
confidence: 99%
“…Many centers have replaced the transnasal route with an endoscopic endonasal approach (37), but both methods can be effective (38). Successful resection is most likely when performed by an experienced neurosurgeon who has a high volume of these cases.…”
Section: Evidencementioning
confidence: 99%
“…However, no homogeneity in the type of LDDST, in terms of dexamethasone dose and time, was reported across different studies. Indeed, some authors performed a 1-mg overnight LDDST (14,120,126,134,139,140,145,165,166,169), whereas other authors performed a 2-mg overnight or 2-mg 2-day LDDST (102,103,109,160,161,164,167,170,171). However, only a few studies have used exclusively this parameter to evaluate disease remission (146,169,171).…”
Section: Dexamethasone Suppression Testmentioning
confidence: 99%
“…One study compared microscopic and endoscopic surgery for CD and found no difference in the remission rate between these two methods. 16 Many of microscopic series for CD have long-term follow-up and report recurrence rates up to 14%. 17 Starke and colleagues report a recurrence rate of 11% at 1 year, and Wagenmakers and colleagues report a rate of 16% at an average follow-up of 71 months.…”
Section: Outcomes For Remission Of Hormone-secreting Tumors Cushing Dmentioning
confidence: 99%